ANALYSIS OF THE DETERMINANTS OF ENTREPRENEURIAL INTENTION OF ACCOUNTING STUDENTS USING THE THEORY OF PLANNED BEHAVIOR APPROACH - Rizki Ramadhan; Lilik Purwanti; Diwayana Putri Nasution; Alya Putri (ZILLZELL MEDIA PRIMA, 2025)
This study explores the factors influencing accounting students’ interest in entrepreneurship through a qualitative interpretive approach. Motivated by Indonesia’s relatively low entrepreneurship ratio of 3.74% compared to neighboring countries, the research seeks to understand why students’ entrepreneurial interest remains limited despite compulsory entrepreneurship courses and growing business opportunities. Using a descriptive qualitative design, data were collected through in-depth interviews and observations of 30 accounting students from the 2022 intake at Aceh Polytechnic and analyzed thematically. The results show that entrepreneurial motivation marked by hard work, perseverance, resilience, and goal commitment and entrepreneurial knowledge covering business fundamentals, risk management, opportunity recognition, and digital business practices significantly shape students’ entrepreneurial interest. The study concludes that entrepreneurial intention arises from the interaction of psychological, educational, and environmental factors, emphasizing the need to strengthen motivation and entrepreneurship education to cultivate innovative, self-reliant, and opportunity-driven graduates who contribute to sustainable economic development in Indonesia.